Achieving excellent dispersion and electrical conductivity of olefin block copolymer/MWCNTs composites efficiently via high-shear processing. (11th August 2017) - Sui, Guopeng; Yu, Wenjin; Zhang, Qin; Chen, Feng; Fu, Qiang
Abstract: Melt blending is a promising and practical method to prepare electrical conductive polymer composites containing multiwalled carbon nanotubes (MWCNTs). The key is to achieve a good dispersion of MWCNTs in polymer matrix. In this study, olefin block copolymer (OBC)/MWCNTs composites were prepared using co-rotating twin-screw extruder with high rotation speed and the influence of screw rotation speed on the dispersion, shortening of MWCNTs and the macro-properties of composites was systematically investigated. It was found that the entangled agglomerates of MWCNTs could be easily destroyed by using high rotation speed and an improved dispersion of MWCNTs was observed as increasing of rotation speed from 50 to 500 rpm. However, with further increasing of rotation speed from 500 to 1000 rpm, no better dispersion was evidenced but a reduction of nanotubes length was detected. As a result, the best electrical conductivity and mechanical properties of OBC/MWCNTs composites were achieved via using the rotation speed of 500 rpm. And the electrical percolation threshold obtained was about 1.5 wt%. This study provides significant guidance for large-scale preparation of conductive composites materials by using co-rotating twin-screw extruder with high rotation speed. Graphical abstract: Highlights: The relationship between rotation speed and the average MWCNT length was systematically studied. The high-shear processing is an efficient method to achieve excellent dispersion of MWCNT in olefin block copolymer. The optimal balance between the dispersion and shortening of MWCNTs was obtained at the rotation speed of 500 rpm.